Analysis of Factors Affecting Regional Original Revenue In Nusa Tenggara Timur (2015-2020) - Yoseph Nanda Fahriza N; Firsty Ramadhona Amalia Lubis; Nurul Azizah Az zakiyyah (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2022)
Regional Original Revenue, namely revenue obtained from various sources located in the region, is collected and managed by the regional government based on the applicable Constitution. The position of East Nusa Tenggara Province's Original Regional Revenue ranks 24th out of a total of 34 provinces. Therefore, the purpose of this study is to analyze the effect of Government Expenditure, GDRP, Total Population, Number of Hotels, and Number of Restaurants on Regional Original Revenue in 22 Regencies/Cities of East Nusa Tenggara Province in 2015-2020. This research uses panel data method, and uses STATA analysis tool. The results of this study indicate that the best model chosen is the Random Effect Model. The GDRP and Population Variables have no significant effect on Regional Original Income. While the variables of Government Expenditure, Number of Hotels and Number of Restaurants have a positive and significant effect on Regional Original Income in the Province of East Nusa Tenggara.